New relevant pesticide transformation products in groundwater detected using target and suspect screening for agricultural and urban micropollutants with LC-HRMS. (15th November 2019) - Kiefer, Karin; Müller, Adrian; Singer, Heinz; Hollender, Juliane
Abstract: Groundwater is a major drinking water resource, but its quality is threatened by a broad variety of anthropogenic micropollutants (MPs), originating from agriculture, industry, or households, and undergoing various transformation processes during subsurface passage. To determine a worst-case impact of pesticide application in agriculture on groundwater quality, a target and suspect screening for more than 300 pesticides and more than 1100 pesticide transformation products (TPs) was performed in 31 Swiss groundwater samples which predominantly originated from areas with intensive agriculture. To assess additional urban contamination sources, more than 250 common urban MPs were quantified. Most of the screened pesticide TPs were experimentally observed by the pesticide producers within the European pesticide registration. To cover very polar pesticide TPs, vacuum-assisted evaporative concentration was used for enrichment, followed by liquid chromatography high-resolution tandem mass spectrometry (LC-HRMS/MS). Based on intensity, isotope pattern, retention time, and in silico fragmentation, the suspect hits were prioritised and verified. We identified 22 suspects unequivocally and five tentatively; 13 TPs are reported here for the first time to be detected in groundwater. In 13 out of 31 groundwater samples, the total concentration of the 20 identified and quantified suspects (1 pesticide and 19 pesticide TPs) exceeded the total concentration of the 519 targets (236 pesticides and TPs; 283 urban MPs) for which we screened. Pesticide TPs had higher concentrations than the parent pesticides, illustrating their importance for groundwater quality. The newly identified very polar chlorothalonil TP R471811 was the only compound detected in all samples with concentrations ranging from 3 to 2700 ng/L. Agricultural MP concentration and detection frequency correlated with agricultural land use in the catchment, except for aquifers, where protective top layers reduced MP transport from the surface. In contrast to agricultural MPs, urban MPs displayed almost no correlation with land use. The dominating entry pathway of urban MPs was river bank filtration. Graphical abstract: Image 1 Highlights: Suspect screening in groundwater revealed 13 new pesticide transformation products. Drinking water quality endangered by chlorothalonil transformation products. 23 of 130 detected compounds (556 quantified) above 0.1 μg/L. Land use and hydrogeological setting strongly drove micropollutant pattern.